Moyuru ōzora - Kitamura, Komatsu 1901-1964 (Tōhō, 2015)
A story of the exploits of the Japanese army pilots during the Sino-Japanese War. The first such film made in Japan to use actual planes, rather than models, for the air warfare sequences
Original: Japan 1940. - Bildformat 4:3
Keywords: Air pilots, Military / Japan / Drama; Sino-Japanese War, 1937-1945 / Aerial operations, Japanese / Drama; Sino-Japanese War (1937-1945); Air pilots, Military; Military operations, Aerial / Japanese; Japan; 1937-1945; War films; Fiction films; Feature films; Drama; Film; DVD-Video